RETRACTED ARTICLE: Physicochemical characteristics of jagung bose, an ethnic staple food from East Nusa Tenggara, Indonesia - Atika Hamaisa; Teti Estiasih; Widya Dwi Rukmi Putri; Kiki Fibrianto (Journal of Ethnic Foods, 2022)
Abstract Jagung bose is a typical corn-based staple meal from East Nusa Tenggara Province, Indonesia, which requires a considerable boiling period due to its hardness. After storage for almost one year, this staple food is prepared from the pena' muti' fatu white corn variety. This study aimed to compare the physicochemical properties of jagung bose to whole corn of the pena' muti' fatu variety. Physicochemical properties analysis consisted of amino acids, functional groups, dietary fiber, proximate, crystallinity, starch granule shape, and pasting properties. In this study, the samples of jagung bose and corn of pena' muti fatu were obtained from the natives in East Nusa Tenggara. Jagung bose was prepared by pounding the kernel to remove the pericarp. The samples were ground and analyzed for physicochemical characteristics, and the data were analyzed by t test. The results showed that whole corn and jagung bose had high amylose and crystallinity and revealed an A-type starch crystal structure. The whole corn had more protein, fat, amylopectin, fiber, and ash but lower starch and amylose content than jagung bose. Starch granules of whole corn and jagung bose were polygonal shape with a smooth surface. The pericarp removal and pounding by adding some water resulted in different pasting properties. The peak, final, and breakdown viscosity and pasting and gelatinization temperatures of whole corn were higher than those of jagung bose. The setback viscosity of jagung bose was lower than that of whole corn, which meant the viscosity was maintained high during cooling. The high gelatinization temperature and crystallinity of jagung bose required a long cooking time.